2005
DOI: 10.1063/1.1944958
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking of Uranium-238 Evaluations against Spherical Transmission and (n,xn)-Reaction Experimental Data

Abstract: The neutron leakage spectra from a thorium sphere of 26 cm outer and 6 cm inner diameters with a central T-D and 252 Cf neutron sources measured at the Institute of Physics and Power Engineering as well as available in the literature measured differential cross sections for Th(n,xn) reaction at 14 MeV were used for benchmarking of the evaluated cross sections from ENDF (versions B-VII.0 and B-VI.8), JEFF-3.1 and Maslov'07 libraries. It was finally concluded that while it is difficult to prefer any of these lib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 5 publications
1
2
0
Order By: Relevance
“…The results of a similar analysis for uranium [13] have shown that the latest 238 U evaluations such as ENDF/B-VII agree with measured data typically within 10%, which is practically equal to experimental uncertainties.…”
Section: Resultssupporting
confidence: 51%
“…The results of a similar analysis for uranium [13] have shown that the latest 238 U evaluations such as ENDF/B-VII agree with measured data typically within 10%, which is practically equal to experimental uncertainties.…”
Section: Resultssupporting
confidence: 51%
“…For JEFF- 3.3 this was the main reason to leave the existing JEFF-3.2 evaluation unchanged and not adopt the outcome of the CIELO project. Neutron leakage spectra from a depleted uranium sphere of 24 cm diameter with a 252 Cf source measured at IPPE [399] are compared with the same libraries. As seen in Fig.…”
Section: Ippe Shielding Experiments For Fe and Umentioning
confidence: 99%
“…Left: a 70 cm ∅ Fe sphere; circles: experiment of L. Trykov[23,398], curves: calculations with JEFF-3.3 (blue curves), JEFF-3.2 (dashed blue) and ENDF/B-VIII.0 (red). Right: a 24 cm ∅ dep U sphere; circles experiment of S. Simakov[399], curves calculations with JEFF-3.3 (blue curve), JEFF-3.2, (dashed blue) and ENDF/B-VIII.0 (red)Fig. 77Řežshielding experiments with iron spheres of varying diameter, a252 Cf neutron source and proton-recoil based detectors.…”
mentioning
confidence: 99%